On the QSPR Models of some Anti-Malaria Drugs using some Reversed Degree-Based Topological Indices (Lafia Journal of Scientific and Industrial Research, 2024)
A topological index is a real number obtained from the chemical structure of a molecular graph that can be used to predict the physiochemical and biological properties of chemical compounds like drugs and benzene structures. This study aimed at proposing a quantitative structure-property relationship (QSPR) model for some physiological and biological properties of some anti-malaria drugs. Some reversed-degree-based topological indices of the molecular graphs of these drugs were computed; hence, a linear regression model analysis of these indices with the empirical values of the said properties of these drugs was carried out and presented. It was found that the topological indices computed for the said drugs have a good correlation with these physicochemical properties.
Keywords: Phamarceutical chemistry; topological indices; anti malaria drugs; QSPR analysis